RETRACTED: Cross-subject integration of biology and ecology in course work - Arbuzova E.N.; Loshenko V.I.; Nazarov S.V.; Poleshchuk P.V.; Sakharov A.V. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001